Derivation and long-term culture of human parthenogenetic embryonic stem cells using human foreskin feeders - Lu, Zhenyu (Springer US, 2010)
PURPOSE: Feeder cells from animals raise considerable concern for contamination because they are directly in contact with embryonic stem cells. METHODS: To address this issue we collected discarded foreskin tissue and prepared a fibroblast cell line. We transferred one parthenogenetic blastocyst on to these feeder cells, and later observed outgrowth. By this approach, we were able to derive a human parthenogenetic embryonic stem cell line successfully. RESULTS: The embryonic stem cells had normal morphology, expressed all expected cell surface markers, could differentiate to embryonic bodies upon culture in vitro, and differentiated further to derivatives of all three germ layers. CONCLUSION: This study indicates that homologous human fibroblasts can be used as feeder cells to support not only the propagation, but also the derivation of ES cells, and this should facilitate studies of therapeutic cloning for research and clinical applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10815-010-9408-5) contains supplementary material, which is available to authorized users.